ANALISIS PENERIMAAN SIMPEN JALU DALAM MENUNJANG KINERJA DINAS PEKERJAAN UMUM KOTA YOGYAKARTA - Fatin Amiroszati; Ferri Wicaksono (Halu Oleo University, 2025)
This study aims to analyse the acceptance of the Public Street Lighting Management Information System (SIMPEN JALU) in supporting the performance of the Yogyakarta City Public Works Office. SIMPEN JALU is part of the effort to implement an Electronic-Based Government System (SPBE), which aims to increase transparency and efficiency in public street lighting (PJU) management. The research method used is a qualitative approach with interview and observation techniques for Yogyakarta City Public Works Office employees. This research uses indicators from the theory of organisational performance proposed by Joan Woodward (1965), with indicators: economical and efficient, effective, fairness and Technology Acceptance Model (TAM) theory by Fred Davis (1989), with indicators: perceived usefulness and perceived ease of use. The results showed that the acceptance of SIMPEN JALU contributed significantly to the performance of the PJU Office, with improvements in data processing, supervision, and faster decision-making. However, challenges such as a lack of training for users and inadequate technology infrastructure still need to be overcome. This research is expected to provide recommendations for the development of SIMPEN JALU to be more optimal in supporting the performance of the Public Works Office of Yogyakarta City, as well as strengthening the implementation of SPBE in the government environment.